Transforming folklore into stage performance: the role of oral literature as local resources for traditional performing arts in Indonesia - Djarot Heru Santosa; Heni Siswantari; Niswi Mukarromah (International Journal of Visual and Performing Arts, 2021)
The transformation of folklore as oral literature is often used for traditional performances. Its function is to strengthen the resilience of a local culture. This research aims to gain better knowledge about the transition process of traditional theatre performances to increase the awareness of the local community. The method used in this research uses a qualitative approach with an explanatory analytical approach and focuses on a multidisciplinary approach that comes from the theory of several branches of science. The results obtained from this study, namely the oral literature of the archipelago, have an important role in historical knowledge. The use of oral literature in stage performances makes a simple story more complex, one of which is manifested in the performing arts of the Dolalak dance. The conclusion that can be drawn is that the transformation of folklore as oral literature into stage performances provides a spiritual experience for the community because it is packaged interestingly through the dance movements. This article will contribute to the use of oral literature as a source of stories in traditional performances so that the results can be used to nurture and maintain the resilience of a local culture